Estimating Production and Warranty Cost at the Early Stage of a New Product Development Project. Issue 1 (2021) - Relich, Marcin; Nielsen, Izabela
Abstract: The paper is concerned with estimating the cost of production and warranty in the context a new product development project. All possible variants of the trade-off between costs are sought within the company's resources and requirements for a product development project. A company and its projects can be specified in terms of variables and constraints that constitute the systems approach for a problem related to cost optimization. This problem is described in the form of a constraint satisfaction problem and implemented with the use of parametric modelling and constraint programming techniques. The paper also presents a method for estimating the cost of prototyping, faulty products in manufacturing and the after-sales stage, and simulating variants that ensure the desirable level of costs. An example shows the applicability of the proposed approach in the context of a product development project.